2014
DOI: 10.1093/infdis/jiu607
|View full text |Cite
|
Sign up to set email alerts
|

Multispecific Aspergillus T Cells Selected by CD137 or CD154 Induce Protective Immune Responses Against the Most Relevant Mold Infections

Abstract: These findings may form the basis for adoptive T-cell transfer for prophylaxis or treatment in patients with these devastating infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 42 publications
4
38
0
2
Order By: Relevance
“…This also precludes the use of multimerized peptide-MHC complexes for isolation of A. fumigatusespecific T cells. Although we and others observed that some isolated A. fumigatus proteins predominantly induce T H 1 responses in healthy individuals, further investigations are needed until these findings could be applied clinically [15,20,21,26]. To overcome the lack of defined antigens for T-cell stimulation, we established a protocol by using a GMP-grade soluble lysate from A. fumigatus, containing the whole spectrum of potential T-cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also precludes the use of multimerized peptide-MHC complexes for isolation of A. fumigatusespecific T cells. Although we and others observed that some isolated A. fumigatus proteins predominantly induce T H 1 responses in healthy individuals, further investigations are needed until these findings could be applied clinically [15,20,21,26]. To overcome the lack of defined antigens for T-cell stimulation, we established a protocol by using a GMP-grade soluble lysate from A. fumigatus, containing the whole spectrum of potential T-cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…This abrogates the risk for phenotypical and functional changes as might occur during a longterm stimulation process (>24 h) [14]. Among several markers described, CD154 (CD40L) and CD137 (4-1BB) fulfill these criteria for CD4þ T cells [14,19,20]. Qualitative differences of expanded A. fumigatusereactive cells selected by CD154 or CD137 were extensively compared in preclinical runs.…”
Section: Depletion Of Cd8þ and Tregsmentioning
confidence: 99%
“…CD40L is a specific marker of CD4+ T cells that have been engaged via T cell receptor stimulation [27]. Impaired expression of CD40L in CD4+ T cells has been reported in HIV-infected individuals compared to healthy controls in response to super-antigen staphylococcal enterotoxin B in vitro [28].…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been used to generate Aspergillus -specific T cells, with in vitro activity against a wide range of fungal isolates [67]. In a further refinement, adoptive transfer of chimeric antigen receptor (CAR) T cells targeting tumor antigens has been adapted to target fungal pathogens [68].…”
Section: Leukocyte Transfusionsmentioning
confidence: 99%